Management systems quality, environment, health & safety: ISO 9001:2000, ISO 14001, OHSAS 18001 - Nag Pranab Kr. (Mumbai Quest, 2002)
This book consists of seven parts-38 chapters which elucidate the technical principles of management systems (ISO 9001:2000, ISO 14001 and OHSAS 18001). It is also given an elaborate self-assessment guide (chapter 23) to examine the feasibility of implem
Keywords: Management systems; Quality control